Biomechanical Comparison of Cannulated Screws vs Nitinol Staple for Tarsometatarsal Fusion in A Cadaveric Model. Issue 1 (January 2022) - Herrin, Alexander S.; Koroneos, Zachary; Elakkari, Sherif T.; Lewis, Gregory; Adebayo, Temitope; Aydogan, Umur
Category: Diabetes; Midfoot/Forefoot Introduction/Purpose: Patients with hallux abducto-valgus typically require first-tarsometatarsal arthrodesis procedures for which the method of fixation is controversial. Nitinol staples have increased in popularity due to their pseudoelastic, and fatigue resistant properties that allow for shape memory. The objective of this study was to evaluate the performance of a Nitinol staple and crossed-screws through three-dimensional diastasis measurements for the first-tarsometatarsal joint in a 4-point bending isolated cadaveric joint model. We tested the hypothesis that a medially applied Nitinol staple would provide the same dynamic stability as crossed-screws while allowing for more physiologic motion. Methods: Seven matched-pairs of lower limb cadaveric specimens were thawed and dissected to isolate the first-tarsometatarsal joint including the first-metatarsal, medial cuneiform, and joint capsule. One specimen from each donor was fixed with a Nitinol staple placed on the medial side of the joint while the other specimen was fixed with two cannulated crossed-screws. Specimens were potted and tested in an MTS test frame (MTS FlexTest 40 MTS, Eden-Prarie, MN) in a 4-point bending setup (Figure 1A) while maintaining a temperature of 37°C. The diastasis between the first-metatarsal and medial cuneiform was measured at two points on the plantar aspect of each bone near the joint (Figure 1B). Specimens were pre-loaded to 10 N, then stepwise increases in cyclic loading performed at 1 Hz and 50 cycles, at 5 N force intervals until failure (complete separation) at the joint occurred. Diastasis measurements were recorded after every 25 N (250 cycles). Results: 3 of 7 matched pairs of specimens have been tested to date. All specimens were able to endure loading up to a peak load of 225 N (2000 cycles) (Figure 1C). At this peak-load, specimens fixed with the Nitinol staple had an average diastasis of 0.79 mm +/- 0.70 mm (average +/- std deviation) versus 0.39 mm +/- 0.16 mm in specimens fixed with screws. Specimens fixed with the staple construct failed at 277 N +/- 51 N whereas those fixed with screws failed 315 N +/- 48 N. Results for 4 additional matched pairs are pending. Conclusion: There has been debate as to whether the rigid fixation of crossed-screws or the compressive shape memory properties of Nitinol staples are advantageous for tarsometatarsal arthrodesis. No previous study has compared the two methods of fixation in a cadaveric model. In this study no significant differences between the two methods have been detected to date. However, other benefits of the staple construct may include decreased procedural time, decreased time under anesthesia, and possible permittance of earlier post-operative weightbearing.